Integration of Science and Islamic Values into Curriculum for Boarding School Students in the Modern Age: Study at An-Nur Hidayatullah Boarding School, Turen-Malang - Azizah, Mar'atul Fitriayu; Rohanita, Lailatur (PT. Riset Press International, 2025)
This article discusses the synergy between science and Islamic values in the curriculum of Islamic boarding schools in the modern era, focusing on implementing project-based learning approaches at the An-Nur Hidayatullah Islamic Boarding School in Turen, Malang. This study explores how project-based activities such as ecoenzymes manufacturing by An Nur Hidayatullah High School students can be understood and studied scientifically while integrating Islamic values into the learning process. Through this approach, students are invited to combine scientific knowledge related to making ecoenzymes with Islamic principles such as concern for the environment, social responsibility, and wise use of natural resources. This study shows that the application of project-based learning provides a practical understanding of scientific concepts and strengthens the formation of Islamic characters relevant to the challenges of the modern era. Thus, the synergy between science and Islamic values in Islamic boarding school education can create a harmonious relationship in educating the younger generation to become intelligent and noble individuals.